Catalytic activities of mammalian epoxide hydrolases with cis and trans fatty acid epoxides relevant to skin barrier function - Yamanashi, Haruto (J Lipid Res, 2018)
Lipoxygenase (LOX)-catalyzed oxidation of the essential fatty acid, linoleate, represents a vital step in construction of the mammalian epidermal permeability barrier. Analysis of epidermal lipids indicates that linoleate is converted to a trihydroxy derivative by hydrolysis of an epoxy-hydroxy precursor. We evaluated different epoxide hydrolase (EH) enzymes in the hydrolysis of skin-relevant fatty acid epoxides and compared the products to those of acid-catalyzed hydrolysis. In the absence of enzyme, exposure to pH 5 or pH 6 at 37°C for 30 min hydrolyzed fatty acid allylic epoxyalcohols to four trihydroxy products. By contrast, human soluble EH [sEH (EPHX2)] and human or murine epoxide hydrolase-3 [EH3 (EPHX3)] hydrolyzed cis or trans allylic epoxides to single diastereomers, identical to the major isomers detected in epidermis. Microsomal EH [mEH (EPHX1)] was inactive with these substrates. At low substrate concentrations (<10 μM), EPHX2 hydrolyzed 14,15-epoxyeicosatrienoic acid (EET) at twice the rate of the epidermal epoxyalcohol, 9R,10R-trans-epoxy-11E-13R-hydroxy-octadecenoic acid, whereas human or murine EPHX3 hydrolyzed the allylic epoxyalcohol at 31-fold and 39-fold higher rates, respectively. These data implicate the activities of EPHX2 and EPHX3 in production of the linoleate triols detected as end products of the 12R-LOX pathway in the epidermis and implicate their functioning in formation of the mammalian water permeability barrier.